KRITIK SASTRA ARAB ERA UMAWY DAN ABBASY - Muhammad Naufal Annabil; Tatik Mariyatut Tasnimah (Universitas Muhammadiyah Gorontalo, 2021)
This writing aims to examine the development of Umawy and Abbasy literary criticism. The method used in collecting data in this historical research is the literature method, the researcher looks for all the data related to this research and then records the data into a notebook. The method used in this research is descriptive qualitative method, this method uses interpretation through descriptive media. Meanwhile, the approach applied in this research is a historical approach, in which the researcher looks for history related to the development of literary criticism in Umawy and Abbasy The results of this study are that we can find out the definition and division of literary criticism, and find out about the purpose of prose and poetry Umawy or Abbasy. In addition, this research produces information about literary criticism in Umawi and Abbasy. In Umawy, literary criticism is still in a developmental stage, whereas in Abbasy, literary criticism is in a perfect state.